Pengaruh Kinerja Keuangan Daerah Terhadap Kemiskinan: Studi Kasus Kabupaten/Kota di Provinsi Sulawesi Tengah - Sri Suartini (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2020)
The distribution of authority to the Regions in managing their regional finances through the implementation of regional autonomy policies expected one of them to encourage the acceleration of poverty reduction. Central Sulawesi Province is one of the provinces that has a high poverty rate. The research aimed to analyze the impact of regional financial performance on poverty levels in various regencies and municipals in Central Sulawesi Province. The analytical method used the econometrics method of panel data analysis. The results indicated that regional financial performance in various regencies and municipals in Central Sulawesi Province did not significantly influence poverty reduction in the region. We suspected that one of them caused by the low ability of regencies and municipals governments in exploring the financial potential of their regions. It was necessary to increase the creativity of regencies and municipals governments in South Sulawesi Province in exploring regional financial resources, including through reforms in the area of taxes and retributions. Besides, regencies and municipals governments of South Sulawesi Province needed to increase alignments, especially in terms of the budget for poverty alleviation programs.